Robert Persons's Conference and the Salic Law debate in France, 1584–1594. Issue 3 (3rd April 2019) - Innes, M. J. M.
ABSTRACT: This article discusses the French debate of the 1580s over the status of the Salic Law and its influence upon an important text in English political thought, Robert Persons's Conference about the next Succession to the Crowne of Ingland. Polemicists on both sides of the conflict between Henri of Navarre and the Catholic League, from Pierre de Belloy to the pseudonymous 'Rossaeus', sought to explain the French royal succession using a concept of custom drawn from Roman law. Custom offered these thinkers a way to explain the Salic Law's peculiar limitation of the succession to males descended agnatically, but it could also be taken to imply that the people, from whom it originated, were in some way superior to the king. The concept was exploited most effectively by Rossaeus, who translated what had been a legal discourse into a freer language of political naturalism. Rossaeus's interpretation of custom was adapted and exploited by Robert Persons in the Conference about the next Succession to the Crowne of Ingland . While, then, much of the Conference's contemporary influence derived from how its argument mapped onto English constitutional geography, it originated as a continuation of League political thought.